Analisis Potensi Likuifaksi Berdasarkan Data Uji Sondir (Cpt) Terhadap Variasi Periode Ulang Gempa Pada Rumah Sakit Di Kota Jambi - intan delfi meilani; Dila Oktarise Dwina; Reguel Mikhail (GLOBAL SCIENTS PUBLISHER, 2026)
Sumatra Island is located in a highly active seismic region, making it vulnerable to soil liquefaction, particularly in loose, saturated granular soils. This condition is of particular concern for critical facilities such as hospitals. This study aims to analyze the liquefaction potential based on Cone Penetration Test (CPT) data under different earthquake return periods at a hospital site in Jambi City. A quantitative approach was employed using secondary data consisting of CPT results, Standard Penetration Test (SPT) data, and Peak Ground Acceleration (PGA) values obtained from the 2024 Indonesian Seismic Hazard Map for return periods of 50, 475, and 2,475 years. Liquefaction potential was evaluated by comparing the Cyclic Stress Ratio (CSR) and Cyclic Resistance Ratio (CRR), followed by the calculation of the Factor of Safety (FS) and the Liquefaction Potential Index (LPI). The results indicate that increasing the earthquake return period leads to higher PGA values, lower FS values, wider distributions of liquefiable soil layers, and higher LPI values. Under the 50-year return period, all soil layers remained stable, whereas the 475-year and 2,475-year return periods produced increasingly extensive liquefaction-prone zones. The S-02 investigation point exhibited a higher liquefaction susceptibility than S-03, with a maximum LPI value of 24.612, although the liquefiable layers at S-03 extended to greater depths. The liquefaction-prone layers were predominantly composed of silt and sand, while clay layers were not interpreted as liquefiable. These findings demonstrate that evaluating multiple earthquakes return periods provides a more comprehensive assessment of soil liquefaction susceptibility and can serve as a valuable reference for foundation design and earthquake risk mitigation in hospital buildings.